Guest People Hakka Identity in China and Abroad - Constable, Nicole (University of Washington Press, 2014)
The essays in this volume analyze and compare what it means to be Hakka in a variety of sociocultural, political, geographical, and historical contexts including Malaysia, Hong Kong, Calcutta, Taiwan, and contemporary China.